Adaptive marker-free registration using a multiple point strategy for real-time and robust endoscope electromagnetic navigation. Issue 2 (February 2015) - Luo, Xiongbiao; Wan, Ying; He, Xiangjian; Mori, Kensaku
<x xml:space="preserve">Abstract</x> Highlights We proposed an adaptive mark-free registration method for aligning electromagnetic trackers and pre-operative images. An endoscope center calibration on the basis of a 2D-printed model was presented. A multiple point strategy was proposed to address an assumption of moving endoscopes along the centerline of the intraluminal organ. The registration error was significantly reduced from 7.58 to 4.71 mm under dynamic phantom validation.